2021
DOI: 10.1111/eth.13145
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic table‐visiting behavior of birds at outdoor restaurants and cafés

Abstract: Fear of humans and its effect on animal behavior is increasingly being recognized as an important structuring force in ecological landscapes, with consequences for ecological interactions and communities. When aggressive, physically dominant species are displaced by anthropogenic disturbance, physically weaker species exploit competitor and predator downtimes to forage in previously risky places. Birds feeding at outdoor restaurants and cafés in association with humans are exposed to fluctuating levels of perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…One of the most ubiquitous food sources for urban sparrows are bar leftovers (Haemig et al, 2015(Haemig et al, , 2021, which in the present study have been shown to have lower nutritional value and a negative impact on their physical condition. Similar nutritionally poor resources can be found around trash containers and rubbish bins spread all over the urban matrix (Bernat-Ponce, Ferrer, et al, 2022;García-Arroyo et al, 2023).…”
Section: Potential Effects Of Studied Urban Diets On Wild House Sparr...mentioning
confidence: 53%
“…One of the most ubiquitous food sources for urban sparrows are bar leftovers (Haemig et al, 2015(Haemig et al, , 2021, which in the present study have been shown to have lower nutritional value and a negative impact on their physical condition. Similar nutritionally poor resources can be found around trash containers and rubbish bins spread all over the urban matrix (Bernat-Ponce, Ferrer, et al, 2022;García-Arroyo et al, 2023).…”
Section: Potential Effects Of Studied Urban Diets On Wild House Sparr...mentioning
confidence: 53%